Unravelling the protein preference of aquatic worms during waste activated sludge degradation. Issue 2 (17th January 2018) - de Valk, Steef; Khadem, Ahmad F.; van Lier, Jules B.; de Kreuk, Merle K.
ABSTRACT: Worm predation (WP) by Tubifex tubifex was investigated using waste activated sludge (WAS) as the substrate. In order to better understand the sludge degradation mechanisms during WP, the activity of five common hydrolytic enzymes was determined and compared among the initial feed activated sludge, endogenous respirated sludge and worm predated sludge. The results showed that the enzymatic activity decreased upon aerobic (worm) treatment of WAS and that this activity was predominantly associated with the removed solids fraction of the sludge. Interestingly, the protease activity showed a smaller decrease in activity when the worms were present. Flow cell cytometry revealed the release of intestinal bacteria from the worms, which are presumed to be largely responsible for the observed protease activity. Additionally, experiments in which T. tubifex were treated with antibiotics showed that the worms are responsible for a maximum of 73% of the observed proteolytic activity. The remaining 27% is attributed to the intestinal bacteria that exhibit a synergistic relationship with T. tubifex towards protein hydrolysis.